Study On The Implementation Of Good Corporate Governance In The Business Sector State Owned Banking In Langkat District - An Suci Azzahra; Mustafa, Mustafa; Annisa Fajariah Damanik (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to examine the implementation of good corporate governance in the business sector state-owned banking in Langkat Regency. This research uses research methods qualitative. The data collection technique used in this research is method observation, interviews and documentation. Data analysis techniques used in research This is a qualitative data analysis technique. The data analysis component used is reduction data (data reduction), data presentation (data display), and drawing conclusions (conclusion drawings). The research results show that the role of internal audit has an influence on implementation of the principles of good corporate governance in the company. Obstacles and Obstacles in implementing Good Corporate Governance in companies, namely the cause is HR knowledge and understanding of GCG principles is still lacking. Lots of human resources who have not attended training, seminars. Apart from that, the principle of transparency is also implemented hampered by inadequate facilities and infrastructure, such as the unavailability of a website. Regarding Independence, Internal Audit at Bank Mandiri is objective in nature carry out audit activities. Apart from that, all internal audit members at the Bank Mandiri Langkat branch, has no family relationship with the Management or staff at the Langkat branch of Bank Mandiri.